2021
DOI: 10.1097/mog.0000000000000795
|View full text |Cite
|
Sign up to set email alerts
|

‘Bumps down under:’ hemorrhoids, skin tags and all things perianal

Abstract: Purpose of reviewThere continues to be a concentrated effort to improve treatment options readily available for some of the most common perianal diseases: hemorrhoids, anal fissure and anal fistula. The emphasis remains on therapies that definitively address the underlying pathology yet minimize pain and risk of incontinence, have a short recovery period, and are cost-effective. In this analysis, recent developments in the literature are reviewed. Recent findingsTreatment of early stage hemorrhoidal disease re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…According to various data, combined diseases of rectum are present in 20-30% of patients who come to a proctologist, with a stable trend towards an increase in their number [4,8,10]. Diagnosis and selection of treatment methods for combined diseases of the rectum represent a complex and still not fully understood problem [1,4,6].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to various data, combined diseases of rectum are present in 20-30% of patients who come to a proctologist, with a stable trend towards an increase in their number [4,8,10]. Diagnosis and selection of treatment methods for combined diseases of the rectum represent a complex and still not fully understood problem [1,4,6].…”
Section: Introductionmentioning
confidence: 99%
“…Hemorrhoids and anal fissure occupy the first and the third places, respectively, in terms of frequency of occurrence among proctological diseases. According to various literary sources, the combination of chronic hemorrhoids with anal fissure is present in 55-70% of patients [1,7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have also shown[2] that sugar can reduce hemorrhoid edema and inflammation. Surgery[3][4] was the main treatment[5][6], but there were more complications such as pain[7], edema, constipation and itching, which affected the quality of life and recovery. This paper focuses on postoperative pain as a complication of systematic discussion.…”
mentioning
confidence: 99%